New Approaches to Building Pathology and Durability - Delgado, João M.P.Q.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents a collection of recent research works intended to assist in the effective management of service loss. It develops and evaluates methodologies for the assessment of defects and failures, and proposes methodologies for preventing and mitigating building defects. As such, the book will appeal to a broad readership of scientists, practitioners, students and lecturers.
Mechanical pathologies of reinforced concrete corbels and repair by bonding composite carbon fabrics -- Assessment and rehabilitation of industrial building for the production of ammonium nitrate low density -- Effect of temperature on water capillary rise coefficient of building materials -- Evaluation of the service life of external painted surfaces applying statistical tools -- Corrosion propagation phase studies on Finnish reinforced concrete façades -- Biocementation as rehabilitation technique -- Natural ageing tests to study in-service different façade solutions - ETICS and premixed one-coat rendered walls -- Prevention of algal growth on clay façades by photocatalytic TiO2 nano-coating -- Rehabilitation of concrete industrial building façades attacked by acids -- Pathologies - Incompatibility of materials and human intervention in a historic building of Elvas.
Keywords: Buildings -- Repair and reconstruction; Buildings -- Maintenance; Building materials; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Cultural property; Building Repair and Maintenance; Building Materials; Structural Materials; Engineering Thermodynamics, Heat and Mass Transfer; Cultural Heritage